Contemporary philosophical works of the mind and the productivity of contemporary fine art - Wissam Abdulkhader Faisal; Ali Sharif Jabr (Basrah Arts Journal, 2023)
This research deals with the conceptual analysis of the mind in its contemporary philosophical form, as the philosophy of mind has increasingly grown through scientific practice that sought to analyze concepts and experimental issues related to the structure and function of the brain. This created a space for distinguishing between different types of mental phenomena from each other, and research About the characteristics that are necessary and sufficient to determine the mentality, which is seen to have the ability to determine mental specificity. Therefore, the research will focus on the most important of those concepts that have been philosophically worked on in defining the concept of the mind. Accordingly, the structure of the research was established within four chapters. The first chapter contained (the framework General) on the research problem, which the researcher summarized by asking (How do the philosophical works of the mind contribute to the production of contemporary art?), and the goal of the research is (to identify the concepts of contemporary philosophy of mind and activate them as analytical mechanisms for contemporary plastic work). As for the second chapter (theoretical framework), it included Two sections: The first section dealt with: (The mind in light of its contemporary problems), and the second section dealt with: (The mind and the works of contemporary philosophers). As for the third chapter (Research procedures), it included defining the research community. (3) artistic works were selected, and the researcher analyzed them as a sample. For the community, while the fourth chapter contained the results and conclusions.